2015
DOI: 10.1007/s00384-015-2349-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk of readmission after laparoscopic vs. open colorectal surgery

Abstract: Despite its technical complexity, LC can be performed without concerns for increased complications or readmission. The shorter length of stay and the lower risk of readmissions underline the true benefits of the laparoscopic approach for colorectal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Whilst LoS after colorectal cancer surgery is generally decreasing, readmission remains a common event, and in some cases the incidence may be rising . Readmission rates are reported to be 11–15% within 30 days rising to 22% by 90 days postdischarge .…”
Section: Introductionmentioning
confidence: 99%
“…Whilst LoS after colorectal cancer surgery is generally decreasing, readmission remains a common event, and in some cases the incidence may be rising . Readmission rates are reported to be 11–15% within 30 days rising to 22% by 90 days postdischarge .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that laparoscopic colectomy is associated with a lower incidence of SSI than open surgery [16][17][18]. In our 2 previous studies [13,14], all patients underwent open surgery for colon cancer.…”
Section: Discussionmentioning
confidence: 79%
“…11,12 The open approach (compared with minimally invasive approach) is used as a surrogate of complexity and was associated with surgical site infectionsas well as higher rates of readmission. 12,13 Another surrogate of operative complexity is case duration, and longer cases are also associated with higher rates of readmission. 13 It is inevitable that more difficult cases are at higher risk for surgical complications; therefore, risk adjustment for operative complexity is crucial for making sound policy decisions and drawing conclusions about surgical outcomes and quality.…”
Section: Implications For Surgical Qualitymentioning
confidence: 99%
“…12,13 Another surrogate of operative complexity is case duration, and longer cases are also associated with higher rates of readmission. 13 It is inevitable that more difficult cases are at higher risk for surgical complications; therefore, risk adjustment for operative complexity is crucial for making sound policy decisions and drawing conclusions about surgical outcomes and quality.…”
Section: Implications For Surgical Qualitymentioning
confidence: 99%